Pencak Silat Bali Kuno Tapak Suci Yogacara Bhumi Sastra Di Tabanan Sebuah Kajian Sosiologi Agama - I Wayan Sudika (Pramana: Jurnal Hasil Penelitian, 2021)
Pencak Silat Tapak Suci Yogacara Bhumi Sastra is one of 72 types of Balinese Traditional Silat; one of them is Paguron Ardha Candra, which was originally named Silat Tapak Sakti. Silat science was developed by Paguron Suling Dewata, with the name Silat Tapak Suci Yogacara Bhumi Sastra. The type of learning is a combination of physical Silat learning (kanoragan) with the holiness of learning. However, it has been successfully preserved today in the holiness learning method. In the society, Balinese Traditional Pencak Silat Tapak Suci Yogacara Bhumi Sastra was agreed to be developed, as one of preserving the original Balinese Culture, because the learning has several functions, such as spiritual, silat, sports and health, preservation, culture, educational, and social. Learning and applying Silat, besides getting Pahala also were protected from Nawa Sanga and Dewa Sethana, to cultivate the seeds of holiness for members, so was spawned individuals person who has more spiritual abilities and has the religious behavior